In the best interest of the child deprived of a family environment: a focus on Islamic Kafalah as an alternative care option - Assim, Usang Maria (University of Pretoria, 2010)
Dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of Prof Julia Sloth-Nielsen, University of the Wstern Cape, South Africa.